THE INFLUENCE OF FINANCIAL INCLUSION AND FINANCIAL BEHAVIOR ON INVESTMENT DECISIONS - Nur Shidik, Yusup Maulana; Kurniawan, Aceng (Universitas Nusa Cendana, 2025)
The research aims to assess the influence of financial inclusion and financial behavior on investment decisions through a survey of MSMEs in West Java. The research method uses a quantitative and descriptive approach with a sample of 400 respondents selected through purposive sampling based on the formula in Slovin with an error tolerance level of 5%. Findings from the research results, both partial and simultaneous, show that financial inclusion and financial behavior positively and significantly influence MSME investment decisions in West Java. Practical implications: It is essential to increase financial inclusion and financial behavior for MSMEs to support more effective investment decisions through operational recommendations, including financial management training, utilization, use, and evaluation of financial product service technology. Theoretically, research is expected to provide benefits for the development of science by recommending verification of findings and expanding the applicability of research results with similar methods and different samples. Keywords: Financial Inclusion; Financial Behavior; Investment Decisions